Professionalism dilemmas, moral distress and the healthcare student: insights from two online UK-wide questionnaire studies. Issue 5 (19th May 2015) - Monrouxe, Lynn V; Rees, Charlotte E; Dennis, Ian; Wells, Stephanie E
Abstract : Objective: To understand the prevalence of healthcare students' witnessing or participating in something that they think unethical (professionalism dilemmas) during workplace learning and examine whether differences exist in moral distress intensity resulting from these experiences according to gender and the frequency of occurrence. Design: Two cross-sectional online questionnaires of UK medical (study 1) and nursing, dentistry, physiotherapy and pharmacy students (study 2) concerning professionalism dilemmas and subsequent distress for (1) Patient dignity and safety breaches; (2) Valid consent for students' learning on patients; and (3) Negative workplace behaviours (eg, student abuse). Participants and setting: 2397 medical (67.4% female) and 1399 other healthcare students (81.1% female) responded. Main results: The most commonly encountered professionalism dilemmas were: student abuse and patient dignity and safety dilemmas. Multinomial and logistic regression identified significant effects for gender and frequency of occurrence. In both studies, men were more likely to classify themselves as experiencing no distress; women were more likely to classify themselves as distressed. Two distinct patterns concerning frequency were apparent: (1) Habituation (study 1): less distress with increased exposure to dilemmas 'justified' for learning; (2) Disturbance (studies 1 and 2): more distress with increased exposure to dilemmas that could not be justified. Conclusions: Tomorrow's healthcare practitioners learn within a workplace in which they frequently encounter dilemmas resulting in distress. Gender differences could be respondents acting according to gendered expectations (eg, males downplaying distress because they are expected to appear tough). Habituation to dilemmas suggests students might balance patient autonomy and right to dignity with their own needs to learn for future patient benefit. Disturbance contests the 'accepted' notion that students become less empathic over time. Future research might examine the strategies that students use to manage their distress, to understand how this impacts of issues such as burnout and/or leaving the profession.